2012
DOI: 10.1002/pssa.201200043
|View full text |Cite
|
Sign up to set email alerts
|

Void properties in silicon heavily doped with arsenic and phosphorus

Abstract: Grown‐in voids in silicon are strongly affected by donor dopants. For As‐doped wafers, voids (revealed as light‐scattering surface defects observed after cleaning) show a pronounced increase in their density up to [As] = 1.7 × 1019 cm−3, but at higher [As] the void density drops sharply. A similar behaviour was found for P‐doped wafers where a sharp drop occurs at [P] > 2.9 × 1019 cm−3. Such a dependence is accounted for by an effect of minor impurity species: vacancy‐impurity complexes (trapped vacancies) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
(16 reference statements)
1
12
0
Order By: Relevance
“…This explains the increase in void counts with increasing doping concentration observed for all three dopants. The sharp reduction of void formation at even higher donor concentration (here observed only for As and P) can be explained assuming that, above a certain concentration, the trapping of interstitials by interstitial‐donor atoms starts dominating over the trapping of vacancies . Other mechanisms, invoking Coulomb repulsive forces between charged vacancies, have also been proposed to explain the suppression of void formation at very high doping concentrations .…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…This explains the increase in void counts with increasing doping concentration observed for all three dopants. The sharp reduction of void formation at even higher donor concentration (here observed only for As and P) can be explained assuming that, above a certain concentration, the trapping of interstitials by interstitial‐donor atoms starts dominating over the trapping of vacancies . Other mechanisms, invoking Coulomb repulsive forces between charged vacancies, have also been proposed to explain the suppression of void formation at very high doping concentrations .…”
Section: Resultssupporting
confidence: 74%
“…Our results have shown that all three donors (P, As, Sb) shift the critical V/G to lower values, moving the point defect equilibrium towards the vacancy‐regime. The increase in vacancy concentration with increasing donor doping can be explained by the formation of dopant‐vacancy complexes, such as SbV or AsV , which act as trapped vacancies and preserve them from annihilation with interstitials, making them available for void formation . This explains the increase in void counts with increasing doping concentration observed for all three dopants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also discussed in literature that the occurrence of structure loss during Cz growth of heavily doped silicon crystals can be affected by oxygen or intrinsic point defects, e.g., [80,84]. High doping concentrations of B, P, and As can have considerable influence on the formation of voids, oxygen precipitates, and the position of the oxidation-induced stacking fault (OSF) ring [84].…”
Section: Constitutional Supercooling In Heavy-doping Cz Growthmentioning
confidence: 99%
“…At high concentrations (10 18 -10 19 atoms/cm 3 ), doping elements such as boron, arsenic, and phosphorus exhibit similar effects on the intrinsic point defect aggregation as nitrogen [84,168,169]. In the case of boron, it was found that the void region as well as the diameter of the OSF ring starts to shrink when the boron content exceeds a level of 5$10 18 atoms/cm 3 .…”
Section: Impact Of Impurities On the Intrinsic Point Defect Aggregationmentioning
confidence: 99%